2011
DOI: 10.1098/rspb.2010.2547
|View full text |Cite
|
Sign up to set email alerts
|

Just a heartbeat away from one's body: interoceptive sensitivity predicts malleability of body-representations

Abstract: Body-awareness relies on the representation of both interoceptive and exteroceptive percepts coming from one's body. However, the exact relationship and possible interaction of interoceptive and exteroceptive systems for body-awareness remain unknown. We sought to understand for the first time, to our knowledge, the interaction between interoceptive and exteroceptive awareness of the body. First, we measured interoceptive awareness with an established heartbeat monitoring task. We, then, used a multi-sensory-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
458
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 447 publications
(546 citation statements)
references
References 23 publications
54
458
8
2
Order By: Relevance
“…This result might tie to weakened sense of limb ownership reflected in a more malleable body representation. Such stronger malleability has been shown using the RHI paradigm in other patients with disorders of the bodily self such as patients with schizophrenia Interestingly, even in healthy participants a weak bodily self awareness is associated with a stronger RHI (Tsakiris, Tajadura-Jimenez, & Costantini, 2011), and experimentally cooling down the temperature of the real hand has been shown to facilitate the RHI (Kammers, Rose, & Haggard, 2011). While the finding of a stronger illusion for participants with xenomelia could suggest reduced proprioception and/or heightened visual capture, such an interpretation has its own caveats: the more pronounced susceptibility was limited to the consciously rated illusion vividness.…”
Section: Resultsmentioning
confidence: 66%
“…This result might tie to weakened sense of limb ownership reflected in a more malleable body representation. Such stronger malleability has been shown using the RHI paradigm in other patients with disorders of the bodily self such as patients with schizophrenia Interestingly, even in healthy participants a weak bodily self awareness is associated with a stronger RHI (Tsakiris, Tajadura-Jimenez, & Costantini, 2011), and experimentally cooling down the temperature of the real hand has been shown to facilitate the RHI (Kammers, Rose, & Haggard, 2011). While the finding of a stronger illusion for participants with xenomelia could suggest reduced proprioception and/or heightened visual capture, such an interpretation has its own caveats: the more pronounced susceptibility was limited to the consciously rated illusion vividness.…”
Section: Resultsmentioning
confidence: 66%
“…Interestingly, a recent study has shown that interoceptive awareness, measured by a heartbeat detection task, is negatively correlated with the intensity of the RHI. Subjects with higher interoceptive awareness were less prone to experience the illusion (Tsakiris, Tajadura-Jiménez, & Costantini, 2011;see Tajadura-Jimenez et al, 2012 for similar results for the ''enfacement'' illusion). This result suggests that subjects with high interoceptive awareness (linked to insula function) are less ready to experience ownership for other stimuli, probably because they have a stronger sense of ownership for their own body.…”
Section: Body Ownership From the Insidementioning
confidence: 80%
“…In the Rubber Hand Illusion, for example, a fake hand can be experienced as one's own if it is stroked at the same time and rate as the genuine (but concealed) body part (Botvinick and Cohen, 1998). Interestingly, people with poor interoceptive sensitivity tend to report a stronger illusion (Tsakiris et al, 2011). A more prosaic example is the illusory sense of motion that is often experienced when sitting on a stationary train and observing a neighboring train depart.…”
Section: Interoception Expectations and The Sense Of Selfmentioning
confidence: 99%